An Exploratory Analysis of Different Problematic Internet Use Profiles in Cybervictims, Cyberbullies, and Cyberbully Victims - Machimbarrena, Juan Manuel; González-Cabrera, Joaquín; Montiel, Irene; Ortega-Barón, Jessica (Mary Ann Liebert Inc., 2022)
The Internet has brought about a paradigm shift in the lives of many people, especially adolescents. While it has opened great possibilities, it has also led to various risks such as cyberbullying and problematic Internet use (PIU). These two constructs have been extensively researched individually and jointly, but the existence of different profiles of problematic use according to the role a person assumes in the context of cyberbullying has not yet been explored. Therefore, the main aim of this study is to analyze the different PIU profiles of those who have been cybervictims, cyberbullies, and cyberbully victims. An analytical and cross-sectional study was conducted on 25,341 adolescents between 10 and 18 years of age (14.60 ± 1.68). The Cyberbullying Triangulation Questionnaire (CTQ) and the Spanish version of the Generalized and Problematic Internet Use Scale-2 (GPIUS2) were used. The results indicate that cybervictims (6.4 percent), cyberbullies (4.3 percent), and cyberbully victims (2.7 percent) have different profiles of PIU (p < 0.001). Two common profiles emerge from the three roles: one of nonproblematic use and the other of severe problematic use. Participants who presented severe problematic use are the ones who obtained higher scores in cybervictimization and cyberaggression, particularly in the case of cyberbully victims. Furthermore, this profile is 7.6 (IC99 percent:6.11-9.44) times more likely to present PIU than noninvolved adolescents. These results are relevant when planning cyberbullying-focused interventions and programs because of the association between cyberbullying and general PIU.
Keywords: adolescents; cyberbullying; cybervictim; internet; problematic use; profiles; Scopus; JCR